Improving Entrepreneurial Competitiveness Through MSMEs Development Strategies in the Era of Globalization - Pratiwi, Ketut Dian Pradnya; Adnyana, I Putu Agus (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to analyze the business development strategy used to enhance the competitiveness of UD. Dian Pertiwi in the era of globalization. A descriptive qualitative approach was employed, utilizing observation, interviews, and documentation as data collection techniques. The findings indicate that UD. Dian Pertiwi implements strategies in three key areas: business capital, service quality, and marketing. Capital management is conducted prudently to ensure operational continuity. Service improvement focuses on delivering friendly and professional interactions to enhance customer satisfaction. Marketing efforts leverage social media platforms to broaden market reach. The study concludes that the implemented business development strategies have effectively contributed to increasing the competitiveness of UD. Dian Pertiwi in facing global market challenges.